Efeitos do treinamento muscular ventilatório sobre o estresse oxidativo em ratos com diabetes mellitus tipo 2 - Silva, Carlos Cassiano Figueiró da (2021)
Diabetes mellitus (DM) is a chronic disease that is on the rise all over the world. It is classified as: type 1 diabetes mellitus (DM 1) and type 2 diabetes mellitus (DM 2). DM 2 is the most prevalent form, resulting in inadequate secretion of pancreatic β cells and increased peripheral insulin resistance, causing hyperglycemia. Hyperglycemia supports the excessive formation of reactive oxygen species (ROS) and causes increased oxidative stress (EO). Ventilatory muscle training (VMT) is a non-pharmacological tool that provides benefits in patients with DM, however the effects on OS and inflammation in the experimental model are not known. Thus, the aim of the present study was to evaluate the effects of VMT on EO in rats with DM 2. Male Wistar rats were used, divided into 4 groups: Group 1: sedentary animals without DM (Sham- Sed); Group 2: trained animals without DM (Sham-VMT); Group 3 sedentary DM animals (DM-Sed) and Group 4: trained DM animals (DM-VMT). DM was induced through a high energy density diet and a low dose of streptozotocin (35 mg/kg), while the animals in the Sham groups received only standard commercial chow. The VMT protocol was performed for 6 weeks, 5 days/week 30min/day. Twenty-four hours after the last day of intervention, the animals were euthanized and blood and tissue samples (heart, lungs, kidneys, diaphragm, gastrocnemius and soleus) were collected, weighed and stored for further analysis. The VMT protocol reduced plasma TBARS levels in DM 2 rats. Regarding antioxidant enzymes, when comparing the Sham-Sed and DM-Sed groups, there was a reduction in MTT in the lungs, NPSH in the heart, lungs and diaphragm, and SOD in the heart, kidneys, gastrocnemius and plasma, characterizing the model experimental DM 2. After the VMT protocol, there was an increase in SOD activity in the lungs and kidneys when comparing the DM-Sed with DM-VMT groups. In conclusion, the VMT protocol reduced oxidant activity in plasma, increased antioxidant activity in lungs and kidneys.